Analysis of Consumer Perception and Preference of Pasteurized Milk on Buying Decision during the COVID-19 Pandemic - Shafiyya, Athaya; Kristanti, Novita Erma; Yuliando, Henry (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2024)
This study was carried out to determine consumer perceptions and preferences of pasteurized milk products with the Susu Nasional brand sold daily by mobile vendors. The influence of these perceptions and preferences on buying decision for Susu Nasional products was directed at the development of a contingency plan for companies during the COVID-19 pandemic. Data were collected through the use of questionnaires and purposive sampling from 20 indicators consisting of 13 exogenous and seven endogenous indicators. The collected data were analyzed using a descriptive statistical method with a partial least square structural equation modeling (PLS-SEM). The results showed a decrease in the buying decision of Susu Nasional products with an increase in the mobile selling implemented by the company due to the vendors’ hospitality, comfort, availability of the product, and the close distance between mobile vendors and customers. On the other hand, the use of attributes by mobile vendors still needs to be increased during the pandemic through the addition of a point of sale by setting up a booth for consumer. In conclusion, PLS-SEM analysis showed that consumer perceptions and preferences positively and significantly influenced 60% of the decision to buy Susu Nasional during the pandemic.